Gut microbiota and tuberculosis infection: interaction and therapeutic potential - Yinghui Chai; Min Li; Xianping Deng; Congcong Ma; Nannan Zhou; Yanan Chen; Yushan Yao; Kang Li; Wenping Gong; Hong Lei (Gut Microbes)
Pulmonary tuberculosis (PTB), caused by Mycobacterium tuberculosis (MTB), is a serious chronic infectious disease. Although significant progress has been made in the prevention and treatment of MTB, current anti-tuberculosis therapies still face numerous challenges. The human gut microbiota, a complex ecosystem, plays a role in host metabolism, immune regulation, and health maintenance. Recent studies have increasingly highlighted a close relationship between gut microbiota and PTB. The gut microbiota, through the gut-lung axis, mediates the immune processes of PTB, while MTB infection can disrupt the ecological balance of the gut microbiome. This review aims to summarize the changes in gut microbiota among PTB patients and their relationship with clinical manifestations, explore the role of gut microbiota in PTB immunity, and further analyze the potential application of gut microbiota therapy in PTB treatment. The goal is to provide clear direction for future research on gut microbiota and lung diseases and propose new strategies for MTB treatment.